Iron regulatory proteins secure iron availability in skeletal muscle to preserve exercise tolerance in heart failure - Chung, Bomee; Jonas, Wenke; Rostami, Fatemeh; Malik, Zulaikha; Szaroszyk, Malgorzata; Lévay, Magdolna; Thackeray, James; Ost, Mario; Nowak, Steven; Hegermann, Jan; Wieland, Thomas; Pich, Andreas; et al. (Cardiovascular research, 2025)
Iron deficiency (ID) is a frequent comorbidity in heart failure (HF) and contributes to exercise intolerance. Tissue iron levels are maintained by cellular iron uptake, sequestration, and release, processes that are tightly controlled by iron regulatory proteins (IRP). Our aim was to explore the role of IRP activity in skeletal muscle function and exercise capacity during HF.We observed that skeletal muscle ID is associated with IRP1 and 2 inactivation 12 weeks after transverse aortic constriction (TAC) in mice with left ventricular (LV) dysfunction and cachexia. To understand the functional implications of IRP inactivation in skeletal muscle, we generated skeletal muscle-specific Irp1/2 knock-out mice (SkM-Irp1/2-KO). These mice developed muscle ID, along with lower transferrin receptor 1 (TFR1) levels and decreased non-haem iron content, within 5 weeks after birth. SkM-Irp1/2-KO mice exhibited shorter running distances and slower velocities during treadmill exercise. Transcriptomic analysis revealed up-regulation of gene clusters associated with endoplasmic reticulum stress, atrophy, mitochondrial dysfunction, and inflammation. Moreover, enhanced glycolysis, increased 18F-deoxyglucose uptake in quadriceps, and faster plasma glucose clearance were detected in SkM-Irp1/2-KO vs. control mice. In contrast, SkM-Irp1/2-KO mice had markedly reduced complex I and II expression, a change that confirmed defects in oxidative phosphorylation.HF leads to IRP1/2 inactivation, ID, and metabolic dysfunction in skeletal muscle in mice. IRP1/2 inactivation in skeletal muscle causes ID, impairs oxidative energy production, and promotes exercise intolerance by reducing the capacity for effective energy utilization.
Gesehen am 20.11.2025